UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PUISI DENGAN PENERAPAN COOPERATIVE LEARNING SISWA KELAS IV SDN. 323 SINUNUKAN II - Elis Sobariah (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Abstract: Efforts to improve kemampuann Reading Poetry, with Implementation Implementation cooperative learning (Coorporatif Learning) fourth grade students of SD Negeri 323 Sinunukan II" The purpose of this study was to determine the ability to read poetry students by using Application of cooperative learning (Coorporatif Learning) Type of Student Team Achievement Division ( STAT) class IV elementary School No. 323 Sinunukan II.Subjek study were all students of Class I as many as 27 people. Type of research is classroom action research with descriptive method of how or techniques that reveal the obvious fact about the symptoms that exist on an object of research. The results showed the students' ability to read poetry by using cooperative learning Implementation of learning (Learning Coorporatif) Type of Student Team Achievement Division (STAD) in the fourth grade Elementary School No. 323 Sinunukan increased to 83.33% of the students are in the Mastery Learning Standards. Keywords : Model Coorporative Learning, Learning Activities, Interests Reading  Results Abstrak : Upaya meningkatkan kemampuann Membaca Puisi, dengan Penerapan Penerapan Pembelajaran Koorperatif (Coorporatif Learning) siswa kelas IV SD Negeri 323 Sinunukan II” Tujuan penelitian ini untuk mengetahui kemampuan membaca puisi siswa dengan menggunakan Penerapan Pembelajaran Koorperatif (Coorporatif Learning) Tipe Student Team Achievment Division (STAT) kelas IV SD Negeri No. 323 Sinunukan II.Subjek penelitian adalah seluruh siswa Kelas I sebanyak 27 orang. Jenis penelitian yang dilakukan adalah penelitian tindakan kelas dengan metode deskriptif yaitu cara atau teknik yang mengungkapkan fakta yang jelas tentang gejala-gejala yang ada pada suatu objek penelitian. Hasil penelitian menunjukan kemampuan siswa membaca puisi dengan menggunakan pembelajaran Penerapan Pembelajaran Koorperatif (Coorporatif Learning) Tipe Student Team Achievment Division (STAD) pada kelas IV SD Negeri No. 323 Sinunukan mengalami peningkatan menjadi 83,33% siswa berada pada Standar Ketuntasan Belajar. Kata kunci : Model Coorporative Learning, Aktivitas Belajar, Hasil Minat Membaca